Determinants of young people's sexual behaviour concerning HIV and AIDS in the practice population of a university health centre in Lagos, Nigeria - Olayinka O. Ayankogbe; Kofo Odusote; Mopelola O. Omoegun; Victoria Ofoha; Ayoade Adedokun; Kehinde O. Abiola (AOSIS, 2011)
Background: AIDS has been a scourge of universities in Africa for a long time. This study was launched at ground-level to fight the dreaded disease by concentrating on young people and to counter the ignorance that surrounds the disease even in numerous African universities. This study of the student community was carried out by family doctors at the University Health Department to determine the prevalence of the determinants of young people's reproductive health behaviour. Objectives: This study is aimed at determining young people's sexual behaviour concerning HIV and AIDS in the practice population of a university in Lagos, Nigeria. Method: Self-administered 63-item questionnaires were distributed amongst 2000 randomly selected students of the University of Lagos, Lagos, Nigeria in September 2005, using a semistructured form of the Comprehensive Youth Survey questionnaire, developed by FOCUS (led by Pathfinder International, Futures Group International and Tulane University School of Public Health). Results: The age distribution of the respondents was designated in the age groups of 15-19 years (15.8%), 20-24 years (60.1%), 25-29 years (19.6%), 30-34 years (2.8%).Demographics of note were that 88.3% of the fathers of the respondents were literate and that 94.5% of the fathers earned more than one US $ per day. The majority of the respondents (99.1%) indicated adherence to one religious faith or the other and 58.8% believed definitely that religion shaped their attitudes about sexual intercourse and sexuality. More than half (64.0%) denied having had sex at all in the three months preceding the study. Furthermore, 68.8% affirmed that it was common amongst friends of their age to use condoms. A significant number of respondents (65.5%) thought that their friends have drunken alcohol. Almost all of the respondents (94.3%) had a positive perception of their family. Conclusion: The Programming for HIV and AIDS Reduction on university campuses in Africa should be conducted comprehensively rather than monothematically and should, take into consideration the five thematic areas of behaviour change communication amongst young people concerning their reproductive health.